Modern Natural Product Synthesis Overcoming Difficulties - Nakada, Masahisa; Tanino, Keiji; Nagasawa, Kazuo; Yokoshima, Satoshi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
In this book, key experts in the field of total synthesis of natural products in Japan describe the details of their synthesis routes including unexpected reactions and syntheses. By presenting detailed stories behind the total synthesis developments, including those routes that were unsuccessful the book provides the reader with a better understanding of how other researchers devise their strategy and overcome difficulties in their studies. The contributions in the book have focused on highlighting the research from Japan however it is appealing to researchers and students worldwide. This compilation of cutting-edge natural product synthesis provides high-quality expertise, especially to graduate students and young researchers, regarding research on synthetic organic chemistry. It can be utilized as teaching material in university seminars as well as provide guidance to researchers in the area of total synthesis. This is an open access book.
1. A Journey to the Total Synthesis of Brasilicardins -- 2. Total Synthesis of Amycolamicin -- 3. Total syntheses using organocatalysis -- 4. Total synthesis of (+)-siladenoserinol A -- 5. Divergent Total Synthesis of Discorhabdins and The Related Marine Natural Products -- 6. Development of Convergent Strategy for Total Synthesis of Hikizimycin -- 7. A Chemoenzymatic Approach for Rapid Assembly of Tetrahydroisoquinoline Alkaloids and Their Analogs -- 8. Synthetic Efforts to Polyphenolic Natural Products -- 9. Total synthesis of alkaloids using practical organocatalytic reactions -- 10. Oxidative Phenolic Coupling Reaction/Aza-Michael Reaction Strategy for Complex Polycyclic Alkaloids -- 11. Enantioselective Total Synthesis of Bioactive Polycyclic Natural Products -- 12. Stereodivergent Synthesis of Skipped Dienes: Development and Application to the Unified Total Synthesis of Madangamine Alkaloids -- 13. Total syntheses of (+)-aquatolideand related humulanolides -- 14. Complex Oligosaccharides Synthesis-Challenges and Tactics- -- 15. Pursuing step economy in total synthesis of complex marine macrolide natural products -- 16. Total synthesis of cochlearol B -- 17. Construction of quinoline N-oxides and synthesis of aurachins A and B: discovery, application, and mechanistic insight -- 18. Total synthesis of avenaol -- 19. Nonbiomimetic Total Synthesis of Polycyclic Alkaloids -- 20. Sequential site-selective functionalization: A strategy for total synthesis of natural glycosides -- 21. Synthetic study of bio-functional glycans -- 22. Total Synthesis of a Marine Bromotriterpenoid Isodehydrothyrsiferol -- 23. Efficient construction of the hexacyclic ring core of palau'amine: the pKa concept for proceeding with unfavorable equilibrium reactions -- 24. A Long Journey towards Structure Revision and Total Synthesis of Amphidinol 3. .
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Natural products; Chemistry; Chemistry, Organic; Medicinal chemistry; Pharmaceutical chemistry; Natural Products; Chemical Synthesis; Organic Chemistry; Medicinal Chemistry; Pharmaceutics